'I didn't want to pass that on to my child, being afraid to go to the dentist': making sense of oral health through narratives of connectedness over the life course. Issue 4 (23rd December 2018) - Emily Kettle, Jennifer; Warren, Lorna; Glenn Robinson, Peter; Walls, Angus; Gibson, Barry John
Abstract: While previous sociological research on oral health has identified the relevance of personal relationships, there is more scope to analyse the mouth through a lens of connectedness. Recent qualitative interviews with 43 older people (65+) in England and Scotland found that participants constructed relational narratives to make sense of their oral health practices. By drawing on ideas of family practices, family display and personal life, we illustrate how the mouth can be understood relationally. Participants presented their own embodied experiences as connected to the actions of their parents. Narratives also reflected how, as parents and grandparents themselves, participants tried to shape the experiences of others. In this way, oral health practices were conceptualised as being about family. This can be seen in self‐narratives that demonstrated how participants located themselves as embedded in webs of ongoing relationships. We highlight the importance of narrated practices of thinking and feeling, whereby participants imagined doing oral health, and indeed family, in different ways. We thereby demonstrate how oral health practices are constituted through family connectedness and at the same time how these practices contribute to the constitution of family. Policy should therefore pay attention to family relations when promoting improvements in oral health practices.